Highly Sensitive Lateral Flow Immunodetection of the Insecticide Imidacloprid in Fruits and Berries Reached by Indirect Antibody–Label Coupling - Lyubov V. Barshevskaya; Elena A. Zvereva; Anatoly V. Zherdev; Boris B. Dzantiev (Foods)
A highly sensitive lateral flow immunoassay (LFIA) for imidacloprid, a widely used neonicotinoid insecticide, has been developed. The LFIA realizes the indirect coupling of anti-imidacloprid antibodies and gold nanoparticle (GNP) labels directly in the course of the assay. For this purpose, the common GNPs conjugate with anti-imidacloprid antibodies and are changed into a combination of non-modified, anti-imidacloprid antibodies, and the GNPs conjugate with anti-species antibodies. The given approach provides the possibility of selecting independent concentrations of GNPs and anti-imidacloprid antibodies to obtain the influence of minimal imidacloprid concentrations in the samples on the formation of detected, labeled immune complexes. A comparative study of imidacloprid LFIAs with common and indirect antibody–label coupling was implemented. The second variant reduced the limit of detection (LOD) of imidacloprid 20 times, reaching 0.2 ng/mL and 0.002 ng/mL for visual and instrumental detection, respectively, thus surpassing the existing LFIAs for imidacloprid. The developed highly sensitive LFIA was tested for imidacloprid detection in freshly squeezed fruits and berries without any additional sample preparation. The imidacloprids revealed were in the range of 75–97% for grape, 75–85% for orange, and 86–97% for apple samples. The time of the testing was 15 min.